Opportunities and obstacles in non-invasive brain stimulation - Toth, Jake; Kurtin, Danielle Lauren; Brosnan, Méadhbh; Arvaneh, Mahnaz (Frontiers in Human Neuroscience, 2024)
Non-invasive brain stimulation (NIBS) is a complex and multifaceted approach to modulating brain activity and holds the potential for broad accessibility. This work discusses the mechanisms of the four distinct approaches to modulating brain activity non-invasively: electrical currents, magnetic fields, light, and ultrasound. We examine the dual stochastic and deterministic nature of brain activity and its implications for NIBS, highlighting the challenges posed by interindividual variability, nebulous dose-response relationships, potential biases and neuroanatomical heterogeneity. Looking forward, we propose five areas of opportunity for future research: closedloop stimulation, consistent stimulation of the intended target region, reducing bias, multimodal approaches and strategies to address low sample sizes.